Pediatric vulvar fibrolipoma - Corimanya-Paredes, Jorge Manuel (2024)
Fibrolipomas have been described as histologic subtypes of lipoma, which are rareand are considered benign mesenchymal neoplasms. They are characterized astumors that occupy the subcutaneous plane and can appear in different parts ofthe body and can be round, oval or multilobulated. There is little literature on thisclinical entity and its occurrence in pediatric age has not been reported. We presentthe case of a giant vulvar tumor in a 2-year-old girl who underwent surgery aftera thorough study supported by Doppler ultrasound and whose histopathologicalresult reported the presence of mature adipose tissue with fibrous tracts, concludingwith the diagnosis of fibrolipoma of the vulva.